SIFAT FISIK TANAH DAN HASIL TANAMAN AKIBAT PEMBERIAN PUPUK ORGANIK PADA SISTEM TUMPANGSARI JAGUNG-KACANG TANAH PADA INCEPTISOL - TRIGUNASIH, NI MADE; KUSMAWATI, TATIEK (Agrotrop : Journal on Agriculture Science; Vol 1 No 1 (2011), 2012)
Soil Physical   Properties and Plant Yield on Organic Fertilizing and Intercropping System of Corn-Peanut on  Inceptisol The experiment was conducted at Pengotan Village, Bangli Regency. The purpose of this experiment was to study  physical   properties of soil organic fertilizer and the intercropping system of corn and peanut on  Inceptisol.The experiment  was arranged in nested  Randomized Block Designed  (RBD)  with three replications. The treatments was consisted of two factors i.e. dosages of organic fertilizers (P) and cropping systems (S). The organic fertilizer treatment consisted of four levels i.e. without fertilizer  (P0),  5  tons  ha   (P1),    10  tons  ha -1 -1 (P2),  and  15  tons  ha (P3).  The treatment of cropping system  consists  of three types i.e. multiplecropping corn and peanut (S1), corn monoculture (S2) and peanut monoculture (S3). The results showed that cropping systems were not significantly influenced to all parameters of soil physical properties, but significantly influenced to the yield of corn and peanuts. The NRR Test indicated that the corn was more profitable on monoculture, but yield of peanut was higher on multiplecropping. Treatment  dosages of  15  tons  ha -1 -1   (P3)  in the  peanut monoculture  provide  the highest fresh  pod weight of 3.13 tons ha . -1
Keywords: organic fertilizer, cropping system, soil physical characters, Inceptisol